MAKNA KONTEKSTUAL PADA MOTTO SKRIPSI MAHASISWA BAHASA DAN SASTRA INDONESIA ANGKATAN 2015 - Munir, Misbahul; Harsono, Harsono (Universitas Madura, 2022)
The history of human civilization shows that language is a form of human behavior that has its own characteristics. Another definition, language is a means of thought, a system of expression that mediates the transmission of thoughts from one person to another. Meaning is a symptom in speech. Contextual meaning is a meaning of a lexeme or word that is in one context. Motto is a word or exclamation that describes the motivation, spirit, and goals of an organization. This research is a qualitative research. Qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects. Based on the results of the discussion, it can be concluded about the Analysis of Contextual Meaning in the Thesis Motto of Indonesian Language and Literature Students Class of 2015 as follows: contextual meaning of setting, contextual meaning of activities, and contextual meaning of relationships.